Resistência e erros inferenciais: Notas sobre as "perturbações" do psicoterapeuta - Vasco, António Branco (1993)
After having reviewed the most commonly used definitions of resistance in the literature, the author concludes for their inadequability, proposing an alternate definition. The present definition decenters the question of resistance from clients while stressing the therapist’s responsibility for the therapeutic impasses. Therapist’s resistance to change is seen not only in terms of the ways he/she understands and formulates clients’ problems, but also in terms of rigidity of adherence of therapeutic techniques and theoretical models. Some of the most common inferential errors (possibly associated with therapist’s resistance) made by therapists during the course of therapy are focused as well as ways to neutralize them.